Exchange rate volatility, corruption, and economic growth - Josefa Ramoni-Perazzi; Héctor Romero (Heliyon, 2022)
This study assesses the impact of exchange rate volatility on economic growth using a panel of 194 countries for the period 1995–2019. We resort to dynamic panel data models considering the exchange rate volatility estimated based on GARCH models as an explanatory variable, along with some control variables such as the level of economic openness and financial development, investment, government spending, and the expected level of education. Countries are grouped according to the level of corruption of the governments. The estimates from both Difference and System Generalized Method of Moments are obtained. The results consistently show a significant negative effect of exchange rate volatility on economic growth, which diminishes as the financial system develops. An important finding is that the effect of volatility is lower in high-corruption countries, which could be because they are used to dealing with the economic instability associated with low levels of governance and incorporate it as part of their costs.